Peran Pengawasan dan Program Efisiensi dalam Mewujudkan Transparansi Pemerintah: Perspektif Good Governance - Utami Priono; Dinar Anggia Putri; Agoestina Mappadang (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
With a focus on spending efficiency, the 2025 state budget planning has started to implement the Presidential Instruction that President Prabowo Subianto of the Republic of Indonesia issued. The goal of this strategy is to guarantee that public monies are used as efficiently as possible and provide real advantages to the community. However, a strong oversight system is necessary to keep an eye on budget allocation and realization to ensure its efficacy. Audits, both internal and external, are essential for encouraging openness and avoiding financial abuse. From the standpoint of good governance, this study attempts to examine how budget efficiency initiatives and monitoring procedures contribute to increased government transparency. Using a literature review approach, the study consults scholarly publications, national regulations, and institutional records. The results show that two interconnected pillars of good governance are efficiency and transparency. A key tool for upholding accountability and focusing efficiency efforts on the interests of the public is effective oversight. Therefore, striking a balance between social justice, efficiency, and service delivery is essential to the government's ability to successfully apply these principles. It is anticipated that this research will further transparent, accountable, and responsive governance.